ASSESSING FREEDOM OF RELIGION PRACTICES: A COMPARATIVE ANALYSIS OF HIJAB BANS IN FRANCE AND COMPULSORY HIJAB IN IRAN AND ACEH, INDONESIA - Oktavian, Zalza Mayu; Batasyam, Saifuddin (Universitas Syiah Kuala, 2024)
This article examines the freedom of religion practices in relation to hijab bans in France under Law No. 2010-199, compulsory hijab in Iran as per the Islamic Penal Code of Iran 1991, and in Aceh province, Indonesia governed by Aceh Government Law (Qanun). The article adopts a juridical-normative approach with a comparative analysis. The findings indicate that the enforcement of compulsory hijab in Aceh, Indonesia aligns with freedom of religion, making it a suitable model for such regulations. Conversely, the French and Iranian governments have faced challenges in addressing discrimination stemming from their respective regulations, thereby violating Article 18 of the Universal Declaration of Human Rights (UDHR) 1948 and the International Covenant on Civil and Political Rights (ICCPR) 1976, as well as Islamic principles and the Maqasid Shariah. The study recommends that the governments of France and Iran reassess their policies on hijab bans and compulsory hijab in accordance with international human rights standards, Islamic values, and the principles of Maqasid Shariah.